In vitro reconstitution of the photosystem I light-harvesting complex LHCI-730: Heterodimerization is required for antenna pigment organization - Schmid, Volkmar H. R. (The National Academy of Sciences of the USA, 1997)
Here we describe the in vitro reconstitution of photosystem I light-harvesting complexes with pigments and proteins (Lhca1 and Lhca4) obtained by overexpression of tomato Lhca genes in Escherichia coli. Using Lhca1 and Lhca4 individually for reconstitution results in monomeric pigment-proteins, whereas a combination thereof yields a dimeric complex. Interactions of the apoproteins is highly specific, as reconstitution of either of the two constituent proteins in combination with a light-harvesting protein of photosystem II does not result in dimerization. The reconstituted Lhca1/4, but not complexes obtained with either Lhca1 or Lhca4 alone, closely resembles the native LHCI-730 dimer from tomato leaves with regard to spectroscopic properties, pigment composition, and stoichiometry. Monomeric complexes of Lhca1 or Lhca4 possess lower pigment/protein ratios, indicating that interactions of the two subunits not only facilitates pigment reorganization but also recruitment of additional pigments. In addition to higher averages of chlorophyll a/b ratios in monomeric complexes than in LHCI-730, comparative fluorescence and CD spectra demonstrate that heterodimerization involves preferential ligation of more chlorophyll b.